Forms of Obligation in Penitentiary Instruction of 19th Century - L. M. Golikov; O. V. Druzhininskaya (Научный диалог, 2019)
The article presents the results of the study of should -constructions in the penitentiary instructions of the 19th century. The relevance of the work is due to the fact that the data obtained will complement the understanding of the means of expression of the category of directivity in the period of formation of the language of penal legislation. The novelty of the work is seen primarily in the fact that the forms of expression of the meaning of obligation are studied in legal discourse as a means of linguistic construction of the legal norm. In addition, the sources are the texts not previously studied from a linguistic standpoint. The article seeks to identify distinctive signs, allowing to differentiate between deontic and non-deontic necessity in legal discourse. Based on the idea that the basic semantic indicator of deontic or non-deontic statements with the meaning of obligation is the nature of the relationship of the subjects of obligation, the authors distinguish between the forms of a normative obligation and a need. The first, having in its syntactic structure the position of an agent, imply the ratio of subjects through the force of coercion. The second, active constructions with non-agentive subject, are determined by the opposition of the subject-addressee of obligation, implementing the modes of need and aspiration, and the subject of voluntariness, which in turn implements a strong-willed impact on an agent that bears an non-normative character.